Nitrogen isotopic ratio across the Galaxy through observations of high-mass star-forming cores. Issue Volume 14:Issue A30(2018) (August 2018) - Colzi, L.; Fontani, F.; Rivilla, V. M.; Sánchez-Monge, A.; Testi, L.; Beltrán, M. T.; Caselli, P.
Abstract: There is a growing evidence that our Sun was born in a rich cluster that also contained massive stars. Therefore, the study of high-mass star-forming regions is key to understand our chemical heritage. In fact, molecules found in comets, in other pristine Solar System bodies and in protoplanetary disks, are enriched in 15 N, because they show a lower 14 N/ 15 N ratio (100-150) with respect to the value representative of the Proto-Solar Nebula (PSN, 441 ± 6), but the reasons of this enrichment cannot be explained by current chemical models. Moreover, the 14 N/ 15 N ratio is important because from it we can learn more about the stellar nucleosynthesis processes that produces both the elements. In this sense observations of star-forming regions are useful to constrain Galactic chemical evolution (GCE) models.